Design of a Subsequent Water Detection System Controlled by the Microcontroller - Chu Yan; Tang Kang; Feng Xiaoming; Cai Xinyuan; Chen Pengju (Institute of Advanced Engineering and Science, 2014)
This article instructs the subsequent water detection system design and implementation of sanitary ware. This system used C8051f040 Microcontroller as the main control module and communication module which controlled the operation of the entire system，touch screen as a position machine，and made use of metal probing technique and weighing sensor technology to realize data test、collection、display、storage and export. At last，the experimental results showed that this system meet the expected requirement and can measure the subsequent water more accurately. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.4140